A New Approach for Sintering Simulation of Irregularly Shaped Powder Particles—Part I: Model Development and Case Studies. Issue 8 (13th February 2022) - Weiner, Max; Schmidtchen, Matthias; Prahl, Ulrich
Abstract : Within the FOR3010 Refrabund project, a new type of composite refractory consisting of alumina and refractory metals such as tantalum and niobium is developed. This material is characterized by its ability to conduct electricity, which offers new opportunities for functional parts in high‐temperature environments. To support the development of material properties and production technology, a new simulation approach is needed, which is able to describe irregularly shaped particles of at least two different phases. Current simulations of sintering processes work often with heavily idealized powder geometries. As sintering is mainly driven by gradients of chemical potential due to surface curvatures, a realistic description of the particle geometry is essential for achieving precise simulation results. Herein, a new approach of modeling the sintering behavior of irregularly shaped powder particles by the use of a finite differences approach is developed. A discrete description of irregular powder particles is introduced, and the diffusional flows at their surfaces and sintering necks as well as their development in time are calculated. The new model is compared with an older model using spherical particle geometries from literature. Comparison with experimental results follows in a subsequent publication. Abstract : Current sintering models often work with spherical particle geometries. However, diffusion and alongside sintering progress are driven mainly by gradients of chemical potential due to surface curvatures. Therefore, the description of particle geometry heavily influences sintering simulation results. In this work, Part I, a sintering model for nonspherical particles is developed and evaluated.